HAMBATAN KONEKSI MATEMATIS SISWA DALAM MATERI OPERASI HITUNG EKSPRESI ALJABAR DI SMP - Ratih Martina Br Siagian; Halini Halini; Hamdani Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2017)
Abstract: This study aims to determine the obstacles of mathematical connections of students in the material of counting algebraic expressions of expression in grade VIII students of SMP Negeri 3 Sungai Raya. The research method used is descriptive with the form of research used is case study. The sample of this research is 30 students of class VIII SMP Negeri 3 Sungai Raya. The result of data analysis indicates that the obstacle of mathematical connection of students in the material of counting operation of algebraic expression there are two obstacle of epistimology that is conceptual barrier and procedural barrier. Based on the results of data analysis found that the level of ability of upper group students only have the connection constraints in reducing the negative number of algebraic expressions, the level of ability of middle group students have barriers in reducing the negative number in algebraic expression and less thorough in solving the problem so there are questions that are not completed , While the level of ability of lower columnok students have obstacles in reducing the negative number, wrong in using the concept, not careful in solving problems in everyday life. Keywords: Connection obstacle, Epistimological obstacle, Algebraic operations